2016
DOI: 10.1021/acs.est.6b02640
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Antibiotic Resistant Bacteria and Resistance Genes by Ozone: From Laboratory Experiments to Full-Scale Wastewater Treatment

Abstract: Ozone, a strong oxidant and disinfectant, seems ideal to cope with future challenges of water treatment, such as micropollutants, multiresistant bacteria (MRB) and even intracellular antibiotic resistance genes (ARG), but information on the latter is scarce. In ozonation experiments we simultaneously determined kinetics and dose-dependent inactivation of Escherichia coli and its plasmid-encoded sulfonamide resistance gene sul1 in different water matrixes. Effects in E. coli were compared to an autochthonous wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(102 citation statements)
references
References 67 publications
(190 reference statements)
9
91
2
Order By: Relevance
“…In this regard, it is advised to define principle-based kinetic parameters for ARG demobilization in clean water matrixes (such as no oxidant demand). At most, few investigations have accurately defined commonly viable rate constants for ARG demobilization, like for ozonation [35] and UV disinfection [39] [52]. To conclude, regardless of huge modern research advance, it remains hard to foresee the demobilization degrees of varying sorts of ARGs throughout wastewater disinfection or oxidation at a changing running technique or water matrix situations [1].…”
Section: Urban Wastewaters Are Established As One Of the Main Originsmentioning
confidence: 99%
“…In this regard, it is advised to define principle-based kinetic parameters for ARG demobilization in clean water matrixes (such as no oxidant demand). At most, few investigations have accurately defined commonly viable rate constants for ARG demobilization, like for ozonation [35] and UV disinfection [39] [52]. To conclude, regardless of huge modern research advance, it remains hard to foresee the demobilization degrees of varying sorts of ARGs throughout wastewater disinfection or oxidation at a changing running technique or water matrix situations [1].…”
Section: Urban Wastewaters Are Established As One Of the Main Originsmentioning
confidence: 99%
“…Although wastewater is treated to eliminate coliform bacteria, treatments may be ineffective at destroying ARGs, resulting in ARG enrichment in surviving wastewater microbes. [55][56][57] Further, functional metagenomic studies (methods described below) have identified increases in phenotypically resistant clones recovered from samples downstream of wastewater treatment plants, suggesting that wastewater treatment and disposal increases the reservoir of resistance mechanisms in the environment. 58 One recent study used metagenomics to better understand ARO and ARG abundance in the Chaobia River, a major source of drinking water, agricultural irrigation, and waste in China.…”
Section: Using Metagenomics To Monitor Environmental and Biological Rmentioning
confidence: 99%
“…In addition, a total ozone dose of 66.0 mgO 3 ·gVSS-1 (ozone dose rate of 3.3 mgO 3 ·gVSS-1·min-1 for a contact time of 20 min) were found to be the most suitable conditions to control filamentous bulking. Czekalski et al (2016) revealed that due to its strong oxidant and disinfectant effects, ozone can be seen as an ideal way to face emerging challenges of water treatment namely multiresistant bacteria (MRB) and even intracellular antibiotic resistance genes (ARG). During their experiment, E. coli inactivation and ARG disruption were noted at specific ozone doses feasible for full-scale application.…”
Section: Ozonationmentioning
confidence: 99%